Impacto económico de la implementación de las energías renovables en La Guajira (2017)
Climate change and energy are closely related. To avoid climate change with high-impact consequences, it is essential to change the current energy model to make it sustainable and this means eliminating the most dangerous and polluting energy sources. Thats' why the department of La Guajira is potentially one of the places for the implementation of these energy systems since it has a very large mining-energy potential. That is why this study seeks to see the economic benefits and externalities that would bring to the department of Guajira the implementation of renewable energy projects. It is expected that this study will estimate the contribution of renewable energies to the national GDP, it is expected that the volume of investment of local and foreign companies in the region will increase, reducing the risk of loss of electricity supply at the national level and to achieve full coverage of the electric power supply in the department of La Guajira. Find possible externalities, both positive and negative of the implementation of renewable energy projects in the social and environmental issues of the department.--Tomado del Formato de Documento de Grado.